Bahasa rojak: Malaysian way of speaking English? / Nor Asni Syahriza Abu Hassan - Abu Hassan, Nor Asni Syahriza (2015)
This conceptual paper discusses the use of informal Malaysian English or famously known as Bahasa Rojak in Malaysia. Bahasa Rojak from academic perspective is defined as a language that results from the combination of different languages. This paper aims to emphasize the differences and similarities between Bahasa Rojak and Manglish, and highlights the factors that influence Malaysian to practice Bahasa Rojak in daily speeches, whether in formal or informal situations, answering the question how does Bahasa Rojak come into existence. This paper also intends to raise the issue relating to Bahasa Rojak which are the effects of having Bahasa Rojak as one of the languages spoken in Malaysia, focusing on whether it leads to the evolution of both languages- Bahasa Malaysia and the English Language or it causes destruction to both languages. This paper also puts forward the view of some academicians regarding the issue of Bahasa Rojak. There are different views and both sides have its own advantages and disadvantages leading to endless debate between both parties. The conclusion summarizes the advantages and the disadvantages of the use of Bahasa Rojak in Malaysia.